2005
DOI: 10.12702/1984-7033.v05n04a10
|View full text |Cite
|
Sign up to set email alerts
|

Selection of sugarcane families and parents by Reml/Blup

Abstract: Were evaluated 113 full-sib families obtained by unbalanced diallel matings in three experiments in an augmented block design (ABD) planted side by side in the same area. The individual and joint analyses of the experiments were performed by the Reml/Blup method. The use of the ABD without replication did not prove adequate in experiments of family selection owing to the low heritability estimate at the level of family means in comparison to the joint analysis of the three experiments. The results presented pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 8 publications
4
35
0
4
Order By: Relevance
“…This result shows that a large portion of the variance was associated to the additive action of the genes. To assess the genetic patterns of sugar cane, Barbosa et al (2005), aimed to predict the additive of genes value for the selection of the parents and the families based on REML/ BLUP analysis in 113 full sib families. The authors showed that the additive genetic effects were predominant for certain characteristics, including the number of culms, average weight of a culm, and ton of sugar cane per hectare (TCH).…”
Section: Resultsmentioning
confidence: 99%
“…This result shows that a large portion of the variance was associated to the additive action of the genes. To assess the genetic patterns of sugar cane, Barbosa et al (2005), aimed to predict the additive of genes value for the selection of the parents and the families based on REML/ BLUP analysis in 113 full sib families. The authors showed that the additive genetic effects were predominant for certain characteristics, including the number of culms, average weight of a culm, and ton of sugar cane per hectare (TCH).…”
Section: Resultsmentioning
confidence: 99%
“…The smaller is the coeffi cient of variation of a trait, the greater is the experimental accuracy. The high coeffi cients of variation can be interpreted with low experimental precision, which affects the inferences that can be made for the observed traits (BARBOSA et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The use of families increases the chances for identifying superior clones and improving the effi ciency in the use of the resources available for conducting the sugar cane breeding program (BARBOSA et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the selection of the best families in sugarcane may be performed as based on the number of stalks (NS), whose heritability based on mean values of families has been greater than the heritability with individual plants, as shown by Kimberg and Cox (2003), Barbosa et al (2005) and Oliveira et al (2008). In addition, its direct effect on SW is of great magnitude.…”
Section: Bp Brasileiromentioning
confidence: 99%